Review of Confucius Doctrine in Korean Legend (Global Scientific Review, 2022)
This article is about the reflection of aspects of Confucianism in Korean mythology. The article reflects many of the issues and values that are part of the doctrine through the unique characteristics of the heroes mentioned in the legend